(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
The article presents the results of a study of the features of the use of thermographic flaw detection for steel building structures, taking into account their actual state under operating conditions. Since these structures are subjected to significant loads, they are subject to failure, including cracking, corrosion, rupture, and other damage. Compliance with the safe operation of steel structures is essential to ensure the safety of personnel and the normal production process. Compliance with safety rules should be regular and systematic, including periodic inspections and diagnosing the condition of steel structures. Thermographic flaw detection methods consists in measuring the surface temperature of a structure using infrared cameras and detecting temperature anomalies that may indicate the presence of defects. The objective of the study is to increase the efficiency of using the active thermography method for examining operated steel structures. Identify possible difficulties that will arise in the application of this method, and develop recommendations to overcome the identified problems. The most significant aspect that can affect the quality of thermographic flaw detection is a characteristic of infrared emission of the investigated structure’s part. The low value of this indicator leads to an increase in the amount of false data, which in turn reduces the reliability of the obtained results. Another equally important part of the work of an engineer in thermographic flaw detection is the choice of the method and place of heating the structure, which depends on specific cases and inspection tasks. Eventually, active thermography may be useful and effective method for flaw detection of steel building structures. However, its application must be carried out in the context of all factors that may affect the accuracy and efficiency of the equipment concerned.